The Advertisement Calls of Two Endangered Species of Endemic Philippine Frogs: (Platymantis spelaeus and P. insulatus (Anura; Ranidae) - Brown, Rafe M.; Dolino, Cynthia N.; Alcala, Ely; Diesmos, Arvin C.; Alcala, Angel C. (Silliman Journal, 2022)
We provide the first published accounts of the acoustic mate-recognition signals of the Negros cave frog, Platymantis spelaeus, and the Gigante Island frog. P insulatus. Both species are endemic to the Visayan Pleistocene Aggregate Island Complex (and are from Negros and Gigante islands, respectively), and both species are considered to be at some level of vulnerability of extinction due to the activities of humans in their very restricted geographical ranges. On the limestone outcrops of the Municipality of Basay in southern Negros Island, P spelaeus calls in and around caves and crevices of porous limestone karst. The mating calls of males of the species are unusually complex, consisting of paired calls of two separate syllables (=notes) each. Each note is a tonal frequency arc, and one portion of the second note is vibrational and amplitude modulated. In paired calls, the first note of the second call possesses relatively rich harmonic structure (up to five distinct harmonics of the fundamental frequency); remaining notes may have up to three harmonics. The Gigante Island group endemic P insulatus still persists despite near complete removal of original vegetation on the islands in this small land-bridge archipelago. Platymantis insulatus calls from crevices and small cave openings in limestone cliffs and outcrops following heavy rains. The mating call of this species is pulsed and highly amplitude-modulated. consisting of a long pulse train, with a gradually increasing pulse rate and decreasing interpulse interval throughout the call until concluding with an extremely rapid final burst of pulses. Each pulse possesses four distinct frequency components and two separate subpulses; examination of expanded waveforms indicates that each pulse is also a brief descending frequency sweep. We compare the mating calls of each species to other taxa in the previously-defined species group to which each belongs and we note call characteristics that uniquely diagnose each species. Call bioacoustics are powerful techniques for studying species-specific behavioral and neurophysiological attributes of a Philippine Frogs; we expect that several more endemic Visayan species may be discovered in the near future through on-going application of these techniques in problems in Philippine frog taxonomy and behavioral ecology.